Meningkatkan Hasil Belajar Tari Melalui Pengembangan Gerak Tari Kreasi di Kelas VIII SMPN Satu Atap 1 Sepang Tahun Ajaran 2022/2023 - via, Selviarianti; Afrom, Ichyatul (FKIP, Universitas Palangka Raya, 2024)
ABSTRAK Pembelajaran adalah perpaduan antara kegiatan, yaitu kegiatan mengajar dan kegiatan belajar. Hasil Belajar adalah perubahan yang dialami siswa sebagai akibat dari mengalami suatu kegiatan belajar. Jenis Penelitian Penelitian yang digunakan dalam penelitian ini adalah Penelitian Tindakan Kelas (PTK). Subjek penelitian ini adalah siswa kelas VIII di SMPN Satu Atap 1 Sepang tahun pelajaran 2023/2024 dengan jumblah siswa 21 orang menggunakan siklus I dan II. Teknik pengumpulan data dilakukan dengan soal pre-test dan praktek gerak. Hasil penelitian menunjukan adanya peningkatan hasil belajar setelah adanya pembelajaran seni tari dengan pendekatan Penelitian Tindakan Kelas (PTK). Berdasarkan hasil pengamatan dan data yang diperoleh pada siklus I, aktivitas peserta didik dengan rata-rata 2,95 dan termasuk dalam kategori cukup baik. Pada siklus II, aktivitas peserta didik dengan rata-rata 3,77 dan termasuk dalam kategori sangat baik. Ada peningkatan hasil belajar peserta didik kelas VIII SMPN Satu Atap Sepang tahun pelajaran 2022/2023 setelah menggunakan model Pembelajaran media video dan praktek pada mata pelajaran SBK ABSTRACT Selviarianti, 2023. Improving Dance Learning Outcomes Through Developing a Variety of Creative Dance Movements in Class VIII of One Roof 1 Sepang State Middle School for the 2022/2023 Academic Year. Thesis, Sendratasik Education Study Program, Department of Language and Arts, Faculty of Teacher Training and Education, Palangka Raya University. Supervisor: (I) Ichyatul Afrom, S.Pd., M.Pd (II) Jimy O. Andin, S.Sn., M.Pd Keywords: Problem Based, Learning Outcomes, Application of Floor Patterns in Dance Movements Learning is a combination of activities, namely teaching activities and learning activities. Learning Outcomes are changes experienced by students as a result of experiencing a learning activity. The type of research used in this research is Classroom Action Research (PTK). The subjects of this research were class VIII students at SMPN Satu Atap 1 Sepang for the 2023/2024 academic year with a total of 21 students using cycles I and II. Data collection techniques were carried out using pre-test questions and movement practice. The research results show that there is an increase in learning outcomes after learning dance using the Classroom Action Research (PTK) approach. Based on the results of observations and data obtained in cycle I, student activity averaged 2.95 and was included in the quite good category. In cycle II, student activity averaged 3.77 and was included in the very good category. There is an increase in the learning outcomes of class VIII students at SMPN One Roof Sepang for the 2022/2023 academic year after using the video and practice media learning model in SBK